Calculation of stresses and strain with the analytical method of pipes in high frequency longitudinal welded pipes: Calculation of stresses and strain with the analytical method of pipes in high frequency longitudinal welded pipes - Mjaku, Malush (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
In general, the different phenomena in the production, the different technological processes, are characterized by one or more factors and indicators. These factors, with their specific nature and with the special way of influencing the phenomena or the different technological processes, give the latter a complex character in practice. During the formation and calibration of the pipes, the thickness and radius of bending of the pipes is very important. It is expected that the smaller the bending radius, the greater the stresses and deformations as a result of the large degree of deformation. To calculate the stresses and deformations, pipes of different thicknesses and diameters were obtained: Ø 139,7×4 mm, Ø 139.7×7.72 mm, Ø 219.1×5 mm, Ø 219.1×8 mm, Ø 244.5×8.94 mm, Ø 323.9×7.10 mm and Ø 323.9×10 mm.